2002
DOI: 10.1297/cpe.11.49
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Birth Weight and Serum Insulin in Obese Children.

Abstract: To reveal the relationship between birth weight and type II diabetes mellitus (DM) in obese children. Obese children (128 boys and 52 girls) with a mean age of 10.3 years were examined. The mean percent relative weight was 48.3% in boys, and 53.7% in girls. The fasting serum level of insulin and fasting plasma glucose were measured, and the homeostasis model assessment (HOMA) was calculated. Maternity record books were used to determine the weeks of gestation and the standard deviation score (SDS) for birth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In children and adolescents from different countries, a relationship between birth weight and both insulin resistance and type 2 DM has been reported (17−20). And in our previous studies, we reported that there was an association between birth weight and blood pressure (BP) in healthy children (21), and between birth weight and insulin resistance or hyperinsulinemia in obese boys (22).…”
Section: Introductionmentioning
confidence: 98%
“…In children and adolescents from different countries, a relationship between birth weight and both insulin resistance and type 2 DM has been reported (17−20). And in our previous studies, we reported that there was an association between birth weight and blood pressure (BP) in healthy children (21), and between birth weight and insulin resistance or hyperinsulinemia in obese boys (22).…”
Section: Introductionmentioning
confidence: 98%
“…Their findings also suggested a high prevalence of diabetes in the "small" birth weight group for women (17.8%), which was higher than those in the "medium" (2.9%) and the birth weight recorded in the maternal and child health handbooks and other related content provided by some participants; and the sub-group analysis with objective birth weight almost showed similar results. Previous studies conducted in Japan have indicated associations between birth weight and adverse conditions such as diabetes and hypertension [34][35][36][37][38][39][40] . However, few epidemiologic studies have targeted middle-aged populations because most reports have focused on individuals during their childhood or young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the association of birth weight with metabolic derangements in obese children in Niigata, Japan (8,9,10,11). We reported the relationships of birth weight and current visceral fat accumulation with hyperinsulinemia and insulin resistance in 967 obese Japanese children and adolescents (650 boys, 317 girls) aged 6 to 15 yr (9).…”
Section: Dohad In Obese Japanese Children and Adolescentsmentioning
confidence: 99%